Health effects of environmental pollutants - Waldbott, George L. (Saint Louis, Missouri : The C.V. Mosby Company, 1978)
The reduction of the the stratospheric ozone layer by fluorocarbon aerosols, the recognition of the carcinogenic property of vinyl chloride (probably the most widely used plastic), the polychlorinated biphenyl (PCB) epidemic in Michigan, and the environment damage from fire-retarding agents are some of the new developments discussed in this revised edition.
Part One: Sources and actions of pollutants -- 1. Disasters -- 2. Pollutants and their sources -- 3. Dispersion of air pollutants -- 4. Recognition of pollutants -- 5. Toxic action of pollutants -- 6. The body's defenses -- 7. Pulmonary irritants -- Part Two: Health effects -- 8. Fibrosis-producing agents -- 9. Granuloma-producing agents -- 10. fever-producing agents -- 11. Asphyxiating pollutants -- 12. Systematic poisons -- 13. Systemic poisons -- 14. Systemic poisons -- 15. Allergenic agents -- 16. Carcinogens -- 17. Mutagenic pollutants -- 18. Economic poisons -- 19. Hydrocarbons -- 20. Pollution by radiation -- 21. Smoking -- 22. Water Pollution -- 23. Noise pollution -- 24. Fires -- 25. Prophylaxis and treatment -- Appendix -- Glossary.
Includes bibliographical references and index.
Keywords: POLLUTION -- TOXICOLOGY